Effect of topical ethanolic extract of noni leaf on post-extraction wound by observation of wound diameter and osteoblast cells - Indah PR. Sabirin; Ris Kristiana; Erick Khristian; Mas KR. Kustiawan; Euis R. Yuslianti (DiscoverSys Inc., 2022)
Objective: The aim of this study is to determine the effect of noni leaf ethanol extract gel on post extraction wound of rabbit teeth observed from wound diameter and osteoblasts cell count. Tooth extraction is one of the treatments performed in the oral region that cause wound. Application of substance or medicine might help accelerate and improve wound healing. Material and Methods: Twenty-four rabbits divided into three groups: negative control, positive control with 10% povidone iodine, and treatment group with 10% ethanol extract gel of noni leaf. The tooth was extracted from the mandibular left incisor. The diameter of the wound area was examined on day 0, 3, 7, and 14 while the osteoblasts cell count was obtained from rabbits’ specimen in each group on 14th day. Measurement of wound diameter was done by using calipers, while the number of osteoblasts were calculated using toluidine blue histochemistry stain and light microscope with 400x magnification. Results: The ratio of wound diameter were better in treatment group with significant difference (p=0.048) while osteoblasts cell count were not significantly different among all groups. Conclusion: Topical application of noni leaf had an effect in decreasing mucosal wound diameter but there was not any evidence yet that it was increased osteoblast cells on socket wound healing process.